2013
DOI: 10.2174/1874325001307010292
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Biomechanical Perspectives on Osteoarthritis and the ACL Deficient Knee: A Critical Review of the Literature

Abstract: This review was undertaken to better understand the debate regarding the issue of osteoarthritis associated with anterior cruciate ligament (ACL) injuries, from a surgical and biomechanical standpoint. Much of the current debate focuses on contributory surgical factors and their relative roles in increasing or decreasing the risk of future osteoarthritis development, primarily highlighting the controversy over whether reconstructive surgery itself is necessarily protective. This review addresses the evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
11
0
1
Order By: Relevance
“…This should be taken into account when observing the effect of animal reconstructive surgery. Arthroscopic procedures are presumed to have less detrimental effect on cartilage compared with extensive open procedures used in animal experiments, which could improve the outcome of ACL reconstruction on the articular cartilage 7 . In animal studies reconstructive ACL arthroscopic procedures are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This should be taken into account when observing the effect of animal reconstructive surgery. Arthroscopic procedures are presumed to have less detrimental effect on cartilage compared with extensive open procedures used in animal experiments, which could improve the outcome of ACL reconstruction on the articular cartilage 7 . In animal studies reconstructive ACL arthroscopic procedures are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several authors have hypothesized that cartilage-loading patterns or surrogate measures of knee-joint health, such as substantial alterations in 3-dimensional (3D) lower extremity joint angles or peak joint moments, may provide key information about the source of poor short-and longterm outcomes after ACLR. 14,15 Assessing and comparing characteristics of lower extremity movement in those with ACLR may provide a more quantitative approach to identifying patients at elevated risk for reinjury and poor long-term joint health. 14,16 Researchers 14,16,17 have hypothesized about which gait characteristics are important for identifying patients at increased risk of injury or developing knee-joint osteoarthritis after ACLR.…”
mentioning
confidence: 99%
“…There is an association between ACL injury and the subsequent development of knee osteoarthritis [7,[30][31][32]. Previous studies have found gait alterations post ACL injury and reconstruction, suggesting that altered kinematics may contribute to the development of knee OA [12][13][14][15]23].…”
Section: Discussionmentioning
confidence: 99%